Merdeka Curriculum vs National Preschool Curriculum Standard : Early Childhood Education Curriculum in Indonesia and Malaysia - Pujianti, Yuli; Sariff, Aimi Farina; Wasliman, Iim; Nuryati, Entin; Fatah, Abdul; Aminah, Siti (Al'Adzkiya Journal, 2024)
The importance of early childhood education as a factor influencing child development and the role of curriculum in improving academic standards form the basis of this study. This study aims to examine and describe the standardized early childhood education (ECE) curriculum in Indonesia and Malaysia. The Merdeka Curriculum in Indonesia and the National Preschool Curriculum Standards in Malaysia are the main subjects of this study. This research uses a qualitative method with comparative analysis. Data were collected from two ECE institutions through documentation studies, interviews, observations and document analysis at TK Negeri Pembina Tingkat Nasional Indonesia and Tadika Kaffah Kids Malaysia. The findings show that both countries prioritize ECE, although in different ways. The Merdeka Curriculum in Indonesia emphasizes flexibility and adaptability to local needs and the uniqueness of Indonesian children, allowing teachers to choose the most appropriate materials and learning approaches. Meanwhile, Malaysia's National Preschool Curriculum Standards are more organized and consistent, focusing on achieving consistent essential academic competencies. In conclusion, both countries can benefit from each other's best practices to improve early childhood education standards despite differences in approach and implementation.